Validation in Art Teacher and Professional Teacher Education Curricula in Finland - Saari Joona; Halttunen Timo; Brauer; Sanna; Mäkelä Marjaana (Open Access Publishing Group, 2022)
Intention and opportunity for validation of competences acquired in different contexts are considered influential to meet the incremental changes in the world of work. Positioned in the universities of applied sciences delivering art and professional teacher education in Finland, we study emergence of validation of prior learning in the intended, or planned, curricula. The Nordic Quality Model for Validation was employed as the empirical frame of reference. Data were collected from the institutions' open websites. The critical discourse analysis revealed differences in curricular discourses between and across the institutions. Texts with more indicators of validation were found within larger providers of professional teacher education, whereas those were more scarce in texts from smaller institutions. Validation texts are shorter in length and more fragmented in art teacher curricula. Despite its centrality in educational policy, validation remains in the margins of art and professional teacher education curricula. It is unlikely that the intended curricula facilitate teacher trainers' efforts to form a shared repertoire of a community of practice in validation of non-formal and informal learning. We suggest further study on the enacted and experienced curricula to examine the role of validation in art teacher and professional teacher education.